Preferred physical characteristics of lidocaine thin film for women with vestibulodynia - Silverstein, R. Gina; Cromeens, Martha Grace; Rowland, Caroline; Ogbansiegbe, Joseph A.; Mihas, Paul; Benhabbour, S. Rahima; Carey, Erin T. (Frontiers in Pain Research, 2023)
Vestibulodynia (VBD) is the most common cause of sexual pain in the United States, affecting up to 15% of reproductive-aged women during their lifetime with limited effective treatment options. This study explores patients' perspective on available treatment options and the ideal characteristics of a vulvar film designed for insertional sexual pain in sexually active women with VBD. There are limited qualitative studies of patients with vulvodynia, despite qualitative methods considered necessary in describing social and relational domains of chronic pain. A better understanding of patient perspectives will help future novel treatment development that will fit the needs of patients with VBD. The current study provides insight into users' responses to key characteristics of loaded film medication, size, shape, flexibility, and application to guide future vulvar film design. Women with VBD expressed an interest in a treatment platform with the potential for greater acceptability and efficacy compared to available topical vulvar regimens.